(3caGjI GdeMJGL aj Mce ESJYeGd GdeMdj hGdOjHGLs ((3eMeO Hf YeQ cfhf s)
(3ChdgG (B:s
(3hHYO deG TGY aj gPG GdReGf dHS GdMQjQ s
(3BNQgG (B:s
(3aEf de jSJWY aHdSGfg de jSJWY aHbdHg hPdc CVYa GdEjeGf hGddg CYde s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs